System zarządzania środowiskowego wg normy ISO 14001 jako stymulator ekoinnowacyjności - oczekiwania i korzyści wewnętrzne przedsiębiorstw - Hajduk, Marzena; Woźniak, Leszek (The Environmental Management System ISO 14001 as the Stimulus of Ecoinnovations - Expected Internal Benefits and the Final Result, 2006)
The implementation of environmental management system in accordance with ISO 14001 gives many benefits. This paper - the result of our own research - shows the most important expected internal benefits and the final outcome of the 18 Polish companies. The working of ISO 14001 system encourages to permanent seeking for innovative solution that could help at environment protection.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 702-709